2000
DOI: 10.1017/s0033291799002731
|View full text |Cite
|
Sign up to set email alerts
|

Elevated circulatory level of GABAA – antagonistic neurosteroids in patients with combat-related post-traumatic stress disorder

Abstract: Chronic CR-PTSD may be associated with increased circulatory level of neuroactive steroids with inhibitory activity at the GABA(A) receptors. Neurosteroid-induced decreased GABAergic tone may be relevant to the symptomatology and pathophysiology of chronic PTSD, as well as to the frequent co-morbidity of PTSD with depression and anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(74 citation statements)
references
References 22 publications
2
71
1
Order By: Relevance
“…Studies of DHEA in patients with stressrelated psychiatric disorders are contradictory, while studies in adult depressed patients showed both increases (Heuser et al, 1998) and decreases as well as no change (Michael et al, 2000;Young et al, 2002) in levels. Studies of DHEA in PTSD have been equally contradictory, with one study citing lower concentrations relative to controls (Kanter et al, 2001) while the other showed elevations (Spivak et al, 2000). We recently measured DHEA and DHEA-S at multiple time points over a 24 h period in women with early abuse and PTSD, and found elevations in both DHEA and DHEA-S (Bremner et al, 2007).…”
Section: Stress and Neurohormonal Systemsmentioning
confidence: 99%
“…Studies of DHEA in patients with stressrelated psychiatric disorders are contradictory, while studies in adult depressed patients showed both increases (Heuser et al, 1998) and decreases as well as no change (Michael et al, 2000;Young et al, 2002) in levels. Studies of DHEA in PTSD have been equally contradictory, with one study citing lower concentrations relative to controls (Kanter et al, 2001) while the other showed elevations (Spivak et al, 2000). We recently measured DHEA and DHEA-S at multiple time points over a 24 h period in women with early abuse and PTSD, and found elevations in both DHEA and DHEA-S (Bremner et al, 2007).…”
Section: Stress and Neurohormonal Systemsmentioning
confidence: 99%
“…DHEA is known to have neuroprotective and functionally enhancing properties in animal studies [49] and has been linked with resilience-related qualities such as self-efficacy, optimism, social support and well-being in a non-clinical sample [50]. We and others have reported increased DHEA and DHEA-S in association with recovery from PTSD in combat veterans [38,51], a finding that has also been observed in civilian trauma survivors with PTSD [14]. More recently, DHEA was demonstrated to have anabolic properties, whereas DHEA-S has been shown to have neuroprotective qualities in warfighters, a fact that has led to treatment trials with DHEA and DHEA-S supplementation during military training [48,52].…”
Section: Resilience-related Prognostic Markersmentioning
confidence: 72%
“…Furthermore, several studies have pointed out that 17-α-OH-P affects some neurological functions; through the activation of GABA A receptor, which exert an inhibitory function on the SNC 46) . Progesterone and its metabolites can induce psychological disorders in men, such as panic attacks 49) , mood disorders (depression and post-traumatic stress disorders) 50) and anxiety 51) . High levels of 17-α-OH-P have also been reported in schizophrenic men 52) .…”
Section: Discussionmentioning
confidence: 99%
“…17-α-O H -P h a s d i r e c t e ff e c t s u p o n t h e p r o c e s s o f spermatogenesis [42][43][44][45] and on the Central Neural System (SNC) where it acts as a positive or a negative modulator of GABA A receptor (γ-amminobutirric-acid A ) 46) ; moreover, it regulates several activities, such as learning, memory 47) and sleep 48) . Furthermore, according to other studies alterations in plasma 17-α-OH-P levels could cause mental health disorders in male subjects, for instance: panic attacks, anxiety, post traumatic stress disorders, depression and schizophrenia [49][50][51][52] . The aim of the study is to evaluate if the occupational exposure to urban pollutants could cause alterations on 17-α-OH-P plasma levels and related diseases in traffic policemen compared to a control group.…”
Section: Introductionmentioning
confidence: 86%